A Cost and Efficiency Analysis of the WALANT Technique for the Management of Trigger Finger in a Procedure Room of a Major City Hospital. Issue 11 (November 2019) - Maliha, Samantha G.; Cohen, Oriana; Jacoby, Adam; Sharma, Sheel
Abstract : Background: The "Wide Awake Local Anesthesia No Tourniquet" (WALANT) technique is gaining popularity in hand surgery owing to its benefits of reduced cost, shorter hospital stay, improved safety, and the ability to perform active intraoperative examinations. The aim of this study is to analyze the cost savings and efficiency of performing A1 pulley release for treatment of trigger finger using the WALANT technique in a major city hospital procedure room (PR) as compared with the standard tourniquet, operating room (OR) approach. Methods: Patients who underwent trigger finger release between 2012 and 2017 were identified. Demographic and procedural information were obtained. Patients were followed for an average of 82 and 242 days in the PR and OR groups, respectively. Results: Thirty-nine PR and 37 OR patients were identified. Case length and turnover time were shorter in the PR group [21.4 ± 7 versus 23.5 ± 14.3 min ( P = 0.942) and 31.1 ± 11.1 and 65.3 ± 17.7 min ( P < 0.001), respectively). The cost of the instrument tray utilized was calculated as $3, 304.25 in the main OR and $993.79 in the PR. Cost per minute for all personal services in the OR was calculated to be $44/min, a cost that was virtually absent in the PR. Complication rates did not differ between both groups. Conclusion: Performing A1 pulley release for treatment of trigger finger using the WALANT technique is both cost effective and time efficient compared to performing the same procedure in the main OR of a major city public hospital.